The study of leptin and leptin receptor expression in infiltrating ductal carcinoma of the breast - Al-Shibli, Saad Mohammed AbdulRazzaq (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Leptin is a multifunctional hormone produced mainly by the white adipocyte. For leptin to act, it needs to bind to its receptor. leptin and its receptor activity is correlated with breast carcinogenesis. The main aim of this study is to investigate the correlation between leptin/leptin receptor and the clinico-pathological features of breast cancer. Fifty one women with breast cancer were included in this study while the control group was 40 women with negative mammogram for breast cancer. Demograghic data, anthropometric measurements and blood samples for serum leptin measurement were taken from all the participants. Leptin level was compared in patients with that of the control. Pre and postoperative leptin levels were studied. We investigated the correlation of leptin and its receptor expression with the clinico-pathological features of the breast cancer through the immunohistochemistry. We localized leptin and its receptor intracellularly using transmission electron microscope (TEM) immunocytochemistry. This study investigates the role of leptin in breast carcinogenesis in many aspects and investigates the subcellular localization of leptin and its receptors in the breast cancerous cells and comparing it with that of normal breast tissue using TEM. No significant differences in leptin levels were obtained in the study group among marital status, parity and menopausal status. Leptin level was significantly high in the study group as compared with the control group; no significant difference was found in leptin levels between the preoperative and postoperative measurements. We found that the majority of the breast cancer cells studied, stained positively for leptin and leptin receptors with co-expression of leptin and its receptors. No significant correlation was found between leptin/leptin receptors expression with the race, menopausal status, lymph node metastasis, estrogen receptor expression, progesterone receptor expression, HER2 expression and tumor size. Majority of the patients with distant metastasis were associated with high leptin and leptin receptor expression. In our study, TEM showed that leptin gold particles are mainly present in the nuclear membrane of the cancerous cells and some particles appeared in the cytoplasm, while the adjacent breast epithelial cells showed that leptin gold particles are scattered all over the cell with much less than that of the cancerous cells. Leptin receptor gold particles are mainly present in the nucleus, nuclear membrane of the cancerous cells and some particles appeared in the cytoplasm as well as the cell membrane; the same pattern was seen in the adjacent breast epithelial cells. In conclusion; leptin may have an important role in the carcinogenesis of breast cancer and in its clinico-pathological features. Attempts to inhibit leptin levels and its expression might help the prevention of breast cancer and its aggressiveness.